Food Grade Nanofiber of Polylactic Acid by Electrospinning: Physicochemical Characterization of Solutions and Parameters of the Technique - Dalila Fernanda Canizales-Rodríguez; Francisco Rodríguez-Félix; José Agustín Tapia-Hernández; Carmen Lizette Del-Toro-Sánchez; Saúl Ruíz-Cruz; Santiago P. Aubourg; Daniela Denisse Castro-Enríquez; Carlos Gregorio Barreras-Urbina; Silvia Elena Burruel-Ibarra; José Luis Pompa-Ramos; Lorena Armenta-Villegas (Journal of Food Quality)
Nowadays, one-third of the world’s food production is wasted, so food industry has focused on the design of new technologies that contribute to preserving food quality and safety, focusing on environmentally friendly packaging. Polylactic acid (PLA) is a polymer which is biocompatible and biodegradable, of low cost, and generally recognized as safe (GRAS) by FDA; on the other hand, nanofibers obtained by electrospinning have the potential food industry application, for protection and release of bioactive compounds, producing active and intelligent packaging and increasing and monitoring food quality. The main objective of this work was to obtain food grade nanofibers (FGNs) of PLA (FGN-PLA) by electrospinning, for which different food grade solutions (FGSs) of PLA (FGS-PLA) concentrations with food grade solvent acetone (FGSA) were made and characterized via viscosity, density, conductivity, surface tension measurements, and rheological properties, and to correlate its effect on the FGN-PLA production by electrospinning as well as the effect of technique process parameters (distance from needle to collector plate and flow rate) on fiber characteristics was investigated. Morphological and dimensional characteristics of fibers were analyzed by SEM; increasing the FGS concentration as from 10% (w/v), beaded free and uniform nanofibers were produced. Also, average diameters increasing at higher polymer concentrations and flow rates. Rheological analysis indicates a Newtonian behavior, and the 10% (w/v) FGS shows stability for electrospinning process. In this paper, we report a detailed investigation of how electrospinning parameters interplay and affect FGN morphology and diameter that can be utilized for future research in food industry, for protection and release of bioactive compounds, as well as to maintain and monitor the food quality, as smart packaging systems.